2018
DOI: 10.1016/j.celrep.2018.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Restriction Extends Lifespan in Progeroid Mice and Alters Lipid and Bile Acid Metabolism

Abstract: SummaryDietary intervention constitutes a feasible approach for modulating metabolism and improving the health span and lifespan. Methionine restriction (MR) delays the appearance of age-related diseases and increases longevity in normal mice. However, the effect of MR on premature aging remains to be elucidated. Here, we describe that MR extends lifespan in two different mouse models of Hutchinson-Gilford progeria syndrome (HGPS) by reversing the transcriptome alterations in inflammation and DNA-damage respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 59 publications
8
115
2
Order By: Relevance
“…The coordinated downregulation of inflammatory genes known to be regulated by STAT3 suggests that the MR‐dependent anti‐inflammatory responses in WAT are being mediated by MR‐dependent inhibition of STAT3 activity . Another group used microarray analyses and found that MR also downregulated STAT3 signaling in the liver of a mouse model of Hutchinson‐Gilford progeria syndrome . To determine whether MR affects STAT3 activity, we measured STAT3 phosphorylation in liver and EWAT of WT and Fgf21 ‐/‐ mice fed a HFD or HFD + MR for 8 weeks (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated downregulation of inflammatory genes known to be regulated by STAT3 suggests that the MR‐dependent anti‐inflammatory responses in WAT are being mediated by MR‐dependent inhibition of STAT3 activity . Another group used microarray analyses and found that MR also downregulated STAT3 signaling in the liver of a mouse model of Hutchinson‐Gilford progeria syndrome . To determine whether MR affects STAT3 activity, we measured STAT3 phosphorylation in liver and EWAT of WT and Fgf21 ‐/‐ mice fed a HFD or HFD + MR for 8 weeks (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic treatments and their effect in Lmna G609G/G609G mice. Given the impressive benefit of the HFD in this mouse model, the finding that methionine restriction (MR), a mimicker of calorie restriction, also extended lifespan seemed puzzling [84]. There, methionine restriction, starting at seven weeks of age in Lmna G609G/G609G mice, increased median lifespan by 20%.…”
Section: Metabolic Approaches In Progeriamentioning
confidence: 99%
“…In an attempt to extend their health span and lifespan, progeroid mice (with either the Lmna G609G/G609G or zmpste24 −/genotypes) were subjected to lifelong methionine restriction from weaning to death [1]. Although this dietary intervention reduces the growth rate of the mice, it does prolong their median and maximum longevity by approximately 20%, commensurate with the observation that methionine restriction also attenuates signs of premature aging such as skeletal aberrations (lordokyphosis and osteoporosis) or fibrosis of the aorta and skeleton muscles.…”
mentioning
confidence: 99%